1997
DOI: 10.1136/jmg.34.8.656
|View full text |Cite
|
Sign up to set email alerts
|

Waardenburg syndrome.

Abstract: Auditory-pigmentary syndromes are caused by physical absence of melanocytes from the skin, hair, eyes, or the stria vascularis of the cochlea. Dominantly inherited examples with patchy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
376
1
24

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(427 citation statements)
references
References 58 publications
(7 reference statements)
4
376
1
24
Order By: Relevance
“…Thus, the mouse mutation Micropthalmia and the human auditory-pigmentary Waardenberg Syndromes (Boissy et al, 1997;Read and Newton, 1997) are found to have mutations in the Mitf bHLH-zip transcription factor which is crucial for neural crest lineage determination and for the regulation of several melanocyte-speci®c genes (Opdecamp et al, 1997;Yasumoto et al, 1995). Interestingly, somewhat similar phenotypes are seen in the Splotch mutant and certain variants of WS which carry mutations in the paired homeodomain protein Pax3 (Read and Newton, 1997), which itself appears to be a positive regulator of Mitf expression (Watanabe et al, 1998). Our data would suggest that c-Myb, or another Myb factor whose function is being mimicked or in¯uenced by v-Myb, at least controls entry into melanocyte di erentiation, but it remains possible that it also regulates commitment to the lineage.…”
Section: C-myb In Relation To Other Transcription Factors Involved Inmentioning
confidence: 99%
“…Thus, the mouse mutation Micropthalmia and the human auditory-pigmentary Waardenberg Syndromes (Boissy et al, 1997;Read and Newton, 1997) are found to have mutations in the Mitf bHLH-zip transcription factor which is crucial for neural crest lineage determination and for the regulation of several melanocyte-speci®c genes (Opdecamp et al, 1997;Yasumoto et al, 1995). Interestingly, somewhat similar phenotypes are seen in the Splotch mutant and certain variants of WS which carry mutations in the paired homeodomain protein Pax3 (Read and Newton, 1997), which itself appears to be a positive regulator of Mitf expression (Watanabe et al, 1998). Our data would suggest that c-Myb, or another Myb factor whose function is being mimicked or in¯uenced by v-Myb, at least controls entry into melanocyte di erentiation, but it remains possible that it also regulates commitment to the lineage.…”
Section: C-myb In Relation To Other Transcription Factors Involved Inmentioning
confidence: 99%
“…In Waardenburg syndrome type 2, mutation of microphthalmia-associated transcription factor is considered to be a central event leading to the dysfunction or loss of melanocytes (10,11). Recently, the c-kit signaling pathway was found to be upstream of microphthalmia-associated transcription factor transcription through phosphorylation by MAP kinase (MAPK) (12).…”
mentioning
confidence: 99%
“…A medida da distopia cantorum foi obtida através do cálculo do índice W, resultante de uma análise envolvendo a medida de três pontos anatô-micos entre os dois olhos, conforme a figura 4. A distopia está presente quando o índice W resulta em valor maior ou igual a 1,95 mm (4) . Exames otológicos envolveram otoscopia, impedanciometria e audiometria computadorizada.…”
Section: Famíliaunclassified
“…Diante desta diversidade clínica, foram propostos os critérios diagnósticos maiores para a SW: perda auditiva neurossensorial, alterações na pigmentação da íris, hipopigmentação do cabelo (topete branco ou cabelos grisalhos surgidos antes dos 30 anos de idade) e distopia cantorum, além de critérios menores: sinófris, hipopigmentação da pele e uma base larga do nariz (4)(5)(6)(7)(8) . Para ter a confirmação da SW o paciente deve apresentar dois critérios maiores e um menor (4) .…”
Section: Introductionunclassified
See 1 more Smart Citation